ADRENAL CORTICAL CARCINOMA WITH HYPERALDOSTERONISM – A CASE REPORT. (February 2015) - Luk, Peter P.; Benbow, Jennifer; Latt, Mark D.; Tabet, Eddy; Chua, Elizabeth; Wu, Ted; Crawford, Michael; McKenzie, Catriona
Abstract : Introduction: Adrenal cortical carcinoma is a rare malignant tumour with an incidence of 1–2 cases per 1 million people. Up to 60% of patients show hormonal symptoms due to excess glucocorticoid and/or androgen production. Case report: An 86-year-old female presented with acute abdominal pain. She had hypokalaemia (2.2 mmol/L) refractory to electrolyte replacement. Her aldosterone level was > 90, 000 pmol/L (normal < 630 pmol/L). ACTH and androgen levels as well as 24-hour urinary cortisol were normal. CT showed a 12 cm right adrenal mass compressing the right lobe of liver. Open resection of the mass with en bloc segment of liver was performed. Pathological findings: Macroscopically, there was a 130 mm lobulated, centrally necrotic tumour adherent to the liver. Microscopically, the tumour was composed of sheets of epithelioid cells with marked nuclear pleomorphism, frequent mitoses including atypical forms as well as areas of haemorrhage, necrosis and calcification. The tumour was positive for inhibin and Melan A, and negative for cytokeratin. The tumour was diagnosed as adrenal cortical carcinoma (pT2NxMx, Stage II). Discussion: This tumour shows histological features of malignancy according to the Weiss criteria. Pure hyperaldosteronism is extremely rare in adrenal cortical carcinomas with only approximately 60 reported cases.